Analisa Pengelola Kecerdasan Emosional (EQ) Pelajar Terhadap Perkembangan Teknologi Informasi - Rini Sukmawati Kusuma Wardhani (Jurnal Media Infotama, 2023)
The presence of the digital era requires everyone to be involved and play a role in it, but in essence Information Technology (IT) has many risks because it can have various impacts ranging from positive to negative impacts. Often a person is confronted and made to feel pressured by a problem, this does not rule out the possibility that someone will take action related to how to solve the problem, it is not uncommon for the problems encountered to affect the individual's emotional intelligence. The use of (IT) that is not directed will cause many problems, but if one is wise in controlling emotions in using IT, there will be many benefits, for example in the current era (IT) is often used as material to solve something, especially among students. This research provides an overview of how this is meant. By using a descriptive quantitative method of data obtained from questionnaires, data processing, interpretation analysis.